Management of postpartum haemorrhage reduction by the effective practices in the scope of midwife: a review - Abujarad, Sawsan. A; Ahmad, Md Fauzi; Abdul Hamid, Nor Aziati; FarajAllah, Heba K (American Scientific Publishers, 2018)
Increasing interest in the quality of healthcare has led to the focus of the maternal mortality and morbidity rate reduction. Maternal death is the death of a woman while pregnant or within 42 days of termination of pregnancy. This death could be from any cause related to pregnancy or its management. The primary Postpartum Haemorrhage (PPH) has occupied the highest factor leading to maternal mortality. PPH is the bleeding from the genital tract of 500 ml or more in the first 24 hours following the delivery of the baby. It is also significant to highlight that international medical studies have found that 69% of maternal deaths are avoidable. There is growing agreement among public health professionals that midwifery has an important contribution to provide high-quality maternal and new-born infant care. Poor quality leads to acute and chronic clinical and psychological morbidity. Therefore, new knowledge is needed to eliminate avoidable maternal and new-born mortality and morbidity. Consequently the objective of this study is to provide a review of the PPH causes and investigate and identify the role of skilled midwife in the PPH reduction. Specifically to identify extent level of breast feeding, skin to skin contact and active management of the third stage of labour on PPH. The contents of this paper provide ready-to-refer and ready-to-use information for the researchers working in the field PPH and midwife related practices.